Calculation of the Bohm potential from the solution of the Ermakov equation (BISTUA Revista de la Facultad de Ciencias Básicas, 2023)
Using the Madelung-Bohm formalism of quantum mechanics and taking into account the relationship with the Ermakov equation, in this paper the Ermakov equation is solved in general form and applications related to the simple harmonic oscillator with a dependent potential are presented. of time, in which the Bohm potentials are calculated for each given example.
Keywords: Bohm potential; Ermakov’s equation